2014
DOI: 10.1111/jir.12139
|View full text |Cite
|
Sign up to set email alerts
|

Improving health behaviours of Latina mothers of youths and adults with intellectual and developmental disabilities

Abstract: While additional research is needed to determine long-term effects and to replicate findings, our results suggest that this culturally sensitive health intervention is a promising way to increase health behaviours which may lead to overall good health for Latina mothers who care for children with IDD across the lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…However, there has been virtually no research on the development of health promotion programs for aging parents of adults with developmental disabilities. An exception is the health promotion intervention, known as Caring for Myself, developed for Latina mothers of youth and adults with intellectual and developmental disabilities (Magana, Li, Miranda, & Paradiso de Sayu, 2015). This intervention consists of eight weekly sessions to encourage caregivers to engage in healthy behaviors, such as accessing health care services or relevant medical tests, nutrition, and exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been virtually no research on the development of health promotion programs for aging parents of adults with developmental disabilities. An exception is the health promotion intervention, known as Caring for Myself, developed for Latina mothers of youth and adults with intellectual and developmental disabilities (Magana, Li, Miranda, & Paradiso de Sayu, 2015). This intervention consists of eight weekly sessions to encourage caregivers to engage in healthy behaviors, such as accessing health care services or relevant medical tests, nutrition, and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This intervention consists of eight weekly sessions to encourage caregivers to engage in healthy behaviors, such as accessing health care services or relevant medical tests, nutrition, and exercise. The initial results for this intervention have been promising, reporting that in post-treatment assessment the caregivers felt an increased sense of health-related self-efficacy and reported an increase in preventative health behaviors (Magana et al, 2015). Studies are needed to extend this health promotion intervention to the general population of aging parental caregivers of adults with developmental disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Literature that examined burden experienced by family caregivers of adults with intellectual disabilities identified several factors that may impact on burden. These include the health of the caregivers, ageing of adults with intellectual disabilities, stigma, gender and caregiver support strategies (Al‐Krenawi, Graham, & Al Gharaibeh, ; Bhatia, Srivastava, Gautam, Saha, & Kaur, ; Chou, Pu, Fu, & Kröger, ; Chou, Fu, Lin, & Lee, ; Grey et al, ; Janicki, Zendell, & DeHaven, ; Lewellyn, McConnell, Gething, Cant, & Kendig, ; ; McKensie & McConkey, ; Nam & Park, ).…”
Section: Introductionmentioning
confidence: 99%
“…Intervention participants reported better self-efficacy and self-care, and both intervention and control groups reported less depression symptoms and caregiver burden. 16 Additional cultural research focused on Latina communities found that culturally tailored programs resulted in parental reports of improvement in skills and knowledge. In contrast, Oklahoma's SafeCare program, assessed specifically within the American Indian parent population, found that parents did not perceive culture incompetence in a generalized program.…”
Section: Current Themes In Literaturementioning
confidence: 99%
“…14,15 Cultural adaptation and influence have also been studied. 16,17 Additionally, maternal health, depression and interpersonal relationships have been analyzed. [18][19][20][21][22] Home visitor by profession is of significant focus in the literature, with analyses of community lay persons, paraprofessionals and residents providing varied outcomes.…”
Section: Current Themes In Literaturementioning
confidence: 99%